2017
DOI: 10.2147/jpr.s121810
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy suppresses neuropathic pain induced by chronic constriction injury in rats through the inhibition of TNF-α

Abstract: PurposePregnancy-induced analgesia develops during late pregnancy, but it is unclear whether this analgesia is effective against neuropathic pain. The detailed molecular mechanisms underlying pregnancy-induced analgesia have not been investigated. We examined the antinociceptive effect of pregnancy-induced analgesia in a neuropathic pain model and the expression of tumor necrosis factor (TNF)-α, glial fibrillary acidic protein (GFAP), Iba-1, and c-Fos in the spinal dorsal horn just before parturition.Materials… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…TNF-α is the most common and important proinflammatory factor that mediates pain, especially neuropathic pain, which prompts leukocyte transmigration into the nerves. 14 , 22 IL-6 is an emerging regulator of pathological pain; a variety of pain models has shown elevated expression levels of IL-6 in the spinal cord and dorsal root ganglia. Besides, the administration of IL-6 protein can result in mechanical allodynia and thermal hyperalgesia.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…TNF-α is the most common and important proinflammatory factor that mediates pain, especially neuropathic pain, which prompts leukocyte transmigration into the nerves. 14 , 22 IL-6 is an emerging regulator of pathological pain; a variety of pain models has shown elevated expression levels of IL-6 in the spinal cord and dorsal root ganglia. Besides, the administration of IL-6 protein can result in mechanical allodynia and thermal hyperalgesia.…”
Section: Discussionmentioning
confidence: 99%
“…A series of experiments have proven that late-pregnant mice exhibit efficient resistance to mechanical, thermal and visceral pain, indicating a condition of PIA. 1 , 8 , 13 , 14 , 26 The increase in the nociceptive threshold in the late stage of gestation is beneficial for the mother. Previous studies have shown the effect of maternal antinociception on central and peripheral processing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 21 As a specific marker for astrocytes, GFAP is often used for the detection of astrocytes. During the development of NP, activated astrocytes could release increased amount of GFAP, which might be associated with hyperalgesia and allodynia, 22 and also the maintenance of chronic pain. In this study, the activation of astrocytes occurred in the early stage of CCI, reached the peak until 7 days, and maintained to 14 days after surgery.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, others have found that pregnancy could reduce the pain hypersensitivity produced in the chronic constriction injury model, in which the sciatic nerve is constricted partially with ligature, 40 during late pregnancy in rats. 41 Of note, T cells have been found to be involved critically in pain processing in female but not in male mice, whereas glial cells are critical to pain transmission in male but not in female mice. 15 During pregnancy, the dampening of the immune system to protect the fetus 42 may explain some pregnancy-induced analgesia.…”
Section: Pain and Pregnancymentioning
confidence: 99%